Development of an Education Model for Increasing Husbands' Knowledge about Exclusive Breastfeeding in Makassar City - muliana, Muliana; Stang, Stang; Ahmad, Mardiana; Syam, Aminuddin; Syam, Yuliana; Arifuddin, Sharvianty; Intan Idiana Hassan (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Husbands' knowledge about exclusive breastfeeding (EB) is still low; this causes a lack of support for breastfeeding mothers, which results in low coverage of exclusive breastfeeding. Purpose: to analyze the effect of developing an exclusive breastfeeding education model on increasing husbands' knowledge. The Method of study is a combination of research and development (R&D), Borg and Gall, quasi-experimental, non-equivalent control group design. Population of husbands of pregnant women: sample, husbands of pregnant women who check their pregnancies at the Community Health Center in the third trimester. Purposive sampling of 60 people was divided into two groups; the intervention group received an exclusive breastfeeding education module plus the MCH book, and the control group received the MCH book, with knowledge measurement (pre-test) in the two control groups. Intervention and post-test were carried out once a week for 4 weeks. Data analysis used the Wilcoxon signed-rank test and the Mann-Whitney test. The Results of the study show that there is an effect of giving exclusive breastfeeding education modules on husbands' knowledge, with an overall post-test p-value of 0.000 < 0.05. There was no effect of giving the MCH handbook to the husband's knowledge, p-value 0.391> 0.05. There were differences in knowledge in the two groups, with the mean ranks greater in the intervention group, namely pre-test 32.67 > 28.33, post-test 1 37.35 > 23.65, post-test 2 41.15 > 19.85, and post-test 3 43.78 > 17.22. There is a difference in knowledge between the intervention and control groups. The exclusive breastfeeding education module increases husbands' knowledge about the importance of breastfeeding, especially exclusive breastfeeding. Conclusion: The exclusive breastfeeding education module increases husbands' knowledge about the importance of breastfeeding, especially exclusive breastfeeding, to be used as a health promotion medium in healthcare facilities.